Kwantitatiewe aspekte van padboukontrakte in Suid-Afrika, 1974 tot 1986 - Loots, W. van H.(Wouter van Heerden) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Ing.) -- Universiteit van Stellenbosch, 1988.